Women’s Representation in Paintings from Hamid Karzai’s Era in Afghanistan - Reza Bayramzadeh; Mehdi Mohamadzade; Reza Rafiei Rad (هنر و تمدن شرق, 2023)
Representation of the image of women in Afghan painting is a subject worthy of attention due to the fundamental and ongoing changes in the type of political governments and the diversity of views on women’s issues, as well as the dominance of patriarchy and the limitations that exist about the sanctity of the image of women in religious governments. Also, considering the wide presence of women in the field of painting, both as painters and as subjects of paintings, after Karzai came to power, it became more necessary to investigate and analyze the representation of women in paintings. The current research aims to investigate and analyze the visual representations of women in the works of art created during the administration of Hamid Karzai in Afghanistan, to classify them. The question is how the images of women were represented in paintings during this period. This is a qualitative studying employing a descriptive-analytical method, using library resources and existing archives. The sampling technique was non-random and purposeful. The samples were selected from the works created during this period. Therefore the images of a woman have been in form of portraits and self-portraits, a woman’s body. The images represent women in everyday life. A woman’s image has been a sign of peace, resilience, and motherland and represents the women’s issues in Afghanistan through the combination of traditional and modern paintings. The painters’ stylistic forms of representation of women in paintings are realism, symbolism, and expressionism, with different common themes before and after the Karzai period. The works of the Karzai era in the representation of women are mostly critical and protesting, revealing the extent of women’s suffering and oppression. What is important in the representation of women in this country’s contemporary art is respect and adoration for their position.